Immune Regulation of Human Herpesviruses and Its Implications for Human Transplantation. (24th January 2013) - Smith, C.; Khanna, R.
Abstract : Human herpesviruses including cytomegalovirus, Epstein–Barr virus, HHV6, HHV7, HHV8, Herpes simplex virus (HSV)‐1 and HSV‐2 and varicella zoster virus (VZV) have developed an intricate relationship with the human immune system. This is characterized by the interplay between viral immune evasion mechanisms that promote the establishment of a lifelong persistent infection and the induction of a broad humoral and cellular immune response, which prevents the establishment of viral disease. Understanding the immune parameters that control herpesvirus infection, and the strategies the viruses use to evade immune recognition, has been critical in understanding why immunological dysfunction in transplant patients can lead to disease, and in the development of immunological strategies to prevent and control herpesvirus associated diseases.